A novel approach of cursive signature generation for personal identity. (21st May 2020) - Shin, Jungpil; Rahim, Md Abdur; Islam, Md Rashedul; Yun, Keun Soo
Signatures are used in many situations of daily life. In many non-English-speaking countries like Japan, people are generally not familiar with English and they do not have English signatures in most cases. However, many of them want to learn how to write English in cursive and hope to have an English signature. Thus, this study proposes a technique for generating an English signature. We use a cubic Bezier curve for the cursive connection and an affine transformation to modify the input characters. Modifications were made in the slant, scale, space between the characters and line emphasis. In addition, we added some decorative functions, such as putting a circle around the signature. The system also provided an animation to teach users how to write cursive English and the order of strokes used in a signature. As a result, we were able to provide system-generated signatures that satisfied the users.